1999
DOI: 10.1088/0963-0252/8/4/309
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the E to H transition in a pulsed inductively coupled plasma discharge with internal coil geometry: bi-stability and hysteresis

Abstract: Electrodeless radiofrequency discharges exhibit two modes of operation: a low-density mode in which the power is capacitively coupled to the plasma and which is known as the E-mode, and a higher density mode which is an inductive discharge known as the H-mode. The transition between these modes exhibits hysteresis, i.e. the E to H transition occurs at a different coil current than the reverse H to E transition. Recent theoretical results show that the hysteresis can be qualitatively understood in terms of elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
112
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(119 citation statements)
references
References 15 publications
6
112
1
Order By: Relevance
“…Note that the E-H mode mixing is high in the transition region and the modification of EEDF is most likely in this power region. Since the width of the hysteresis loop is found to be pressure dependent ͑much smaller in the case of low pressure͒, 6,10,23 performing the measurement at one fixed power in E mode will not fairly reflect the similar power coupling conditions. Recently, we have shown that the normalized EEPF immediately before the E to H transition point is identical to the one immediately before the H to E transition point, namely, bi-Maxwellian.…”
Section: Eepf Evolution In E Modementioning
confidence: 96%
See 1 more Smart Citation
“…Note that the E-H mode mixing is high in the transition region and the modification of EEDF is most likely in this power region. Since the width of the hysteresis loop is found to be pressure dependent ͑much smaller in the case of low pressure͒, 6,10,23 performing the measurement at one fixed power in E mode will not fairly reflect the similar power coupling conditions. Recently, we have shown that the normalized EEPF immediately before the E to H transition point is identical to the one immediately before the H to E transition point, namely, bi-Maxwellian.…”
Section: Eepf Evolution In E Modementioning
confidence: 96%
“…23,24 The EEDFs presented in Ref. 23 for pressures 0.67 and 6.7 Pa are reported to be Maxwellian and Druyvesteyn-like, respectively.…”
Section: Eepf Evolution In E Modementioning
confidence: 97%
“…Specifically, for inductively-coupled (IC) discharge plasmas, bistabilities have been studied for a long time, resulting in a large number of reports [97,98,99,100,120,121,119,122,123]. For example, Fig.…”
Section: Optical Bistability Of the Waveguide Nanoplasmamentioning
confidence: 99%
“…Here, the emission yield from an argon plasma shows a strong hysteresis as a function of the coil current. Such bistabilities are commonly explained by considering power balance diagrams, which compare the dissipated with the absorbed power in the IC discharge plasma [119]. In Fig.…”
Section: Optical Bistability Of the Waveguide Nanoplasmamentioning
confidence: 99%
“…In addition, the transition between these two modes has been reported to exhibit hysteresis, i.e., when reducing input power starting in H mode, the transition to E mode occurs at lower powers than the transition to H mode when starting in E mode. 1-8 Hysteresis in the E -H mode transition has been reported, almost exclusively in argon, in the measured optical emission, 1,3,5-7 electrical characteristics, 2-4 plasma density, 3,4,8 and magnetic field 3,4 dependence on coil current or input power. Most often, the studied ICPs have external 1,5,6,8 or internal cylindrical coils 3 but hysteresis has also been reported in external flat coil ICPs.…”
mentioning
confidence: 91%